Perancangan Sistem Kerja Melalui Pendekatan Ergonomi Dengan Metode Cardiovascular Load (CVL) - Danang Ahmad Prayoga; Sajiyo Sajiyo (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
CV. ABP Mandiri is a manufacturing company that produces motorcycle spare parts, particularly swingarm components. The company’s main problem is the absence of standardized working time and inefficient work methods, causing production targets to not be achieved optimally. This study aims to analyze the physical workload level of operators using the Cardiovascular Load (CVL) method in the production process at CV. ABP Mandiri. The CVL method is used to determine the level of work fatigue based on measurements of resting heart rate and working heart rate of operators at each production workstation. Research data were obtained through field observations and direct heart rate measurements during work activities. Based on the results of the study using the CVL method, the operators’ workload level was categorized as low to moderate. The welding process had the highest workload with a CVL value of 53%. Therefore, improvements in the work system, rest time arrangements, and the application of ergonomics are needed to reduce work fatigue and improve operator productivity.